Energy Prices, Pass-Through, and Incidence in U.S. Manufacturing - Sharat Ganapati; Joseph S. Shapiro; Reed Walker (Institute for the Study of Labor (IZA), 2016)
This paper studies how increases in energy input costs for production are split between consumers and producers via changes in product prices (i.e., pass-through). We show that in markets characterized by imperfect competition, marginal cost pass-through, a demand elasticity, and a price-cost markup are sufficient to characterize the relative change in welfare between producers and consumers due to a change in input costs. We find that increases in energy prices lead to higher plant-level marginal costs and output prices but lower markups. This suggests that marginal cost pass-through is incomplete, with estimates centered around 0.7. Our confidence intervals reject both zero pass-through and complete pass-through. We find heterogeneous incidence of changes in input prices across industries, with consumers bearing a smaller share of the burden than standards methods suggest.
Keywords: L11; H22; H23; Q40; Q54; 330; energy prices; incidence; environmental taxation